ANALISIS BIMBINGAN BAGI ANAK TUNA CAKAP BELAJAR DI SEKOLAH DASAR KELAS IV GMIT 05 ADANG. DESA ADANG BUOM KECAMATAN TELUK MUTIARA KAB ALOR - Elisabeth Labe; Dematrius Prabila, Yessy Mata, Petrus Mau Tellu Dony, Jon Abraham Lalang, Yame,Yermia S. Wabang (CV. Adiba Aisha Amira, 2025)
This study aims to examine the forms of guidance provided for children with learning disabilities in Grade IV at SD GMIT 05 Adang, Teluk Mutiara District, Alor Regency. The research employed a qualitative descriptive approach, with data collected through observation and interviews. The results showed that guidance was carried out through both individual and small group approaches, focusing on academic, social, and emotional aspects. Teachers utilized concrete media and gradual repetition of material to enhance students’ understanding. The guidance program also involved collaboration with parents. The impact was evident in the increased student engagement, such as greater confidence in asking questions and developing basic reading and writing skills. However, challenges remained, such as limited facilities and a lack of teacher training in handling students with special needs. Therefore, it can be concluded that appropriate guidance approaches, supported by collaboration among teachers, parents, and counselors, are essential to optimally support students’ learning development.